2022
DOI: 10.1039/d2fo02051c
|View full text |Cite
|
Sign up to set email alerts
|

Jerusalem artichoke inulin supplementation ameliorates hepatic lipid metabolism in type 2 diabetes mellitus mice by modulating the gut microbiota and fecal metabolome

Abstract: The main focus of this study was on the protection mechanism of Jerusalem artichoke inulin (DI) against type 2 diabetes mellitus (T2DM) associated with abnormal hepatic lipid metabolism and gut...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…The higher abundance of Prevotellaceae not only protects intestinal epithelial cells against oxidative stress, thereby, alleviating inflammatory symptoms in patients with inflammatory bowel diseases, but also beneficial for preventing obesity (103,104). Consistent with this study, Jerusalem artichoke inulin also enriched several genera of the Prevotelaceae family, and improved lipid metabolism in type 2 diabetes mice (105). This suggested that Prevotellaceae might be the key family for BI to exert its effect on lipid-lowering.…”
Section: Discussionsupporting
confidence: 84%
“…The higher abundance of Prevotellaceae not only protects intestinal epithelial cells against oxidative stress, thereby, alleviating inflammatory symptoms in patients with inflammatory bowel diseases, but also beneficial for preventing obesity (103,104). Consistent with this study, Jerusalem artichoke inulin also enriched several genera of the Prevotelaceae family, and improved lipid metabolism in type 2 diabetes mice (105). This suggested that Prevotellaceae might be the key family for BI to exert its effect on lipid-lowering.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with these findings, our data revealed that in the HBW group, serum levels of specific PC species, namely PC (20:3/20:1) and PC (22:5/18:3), were significantly elevated and positively correlated with the abundance of Prevotellaceae_UCG-001. Interestingly, the work of Li et al [49] supports the notion that the enrichment of Prevotellaceae_UCG-001 in the intestines of mice, particularly those fed with Jerusalem artichoke and inulin, is closely associated with increased PC levels. Additionally, our study revealed that HBW goat kids exhibit elevated relative concentrations of adipic acid and 2-hydroxymyristic acid.…”
Section: Discussionmentioning
confidence: 86%
“…However, a negative correlation between Blautia and the serum level of Ile was also found. Several studies showed that Dubosiella presented a decreased abundance in T2DM mice and was significantly negatively related to TG, HOMA‐IR, FBG, TC, and LDL‐c (Li et al, 2022; Yin et al, 2022). However, two conflicting reports showed that Dubosiella presented an increased abundance in T2DM mice and was positively correlated with the circulating level of total BCAAs, Val, and Ile (Bao et al, 2022; Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%